Faunal study of velvet ants (Hymenoptera: Mutillidae) and their activity pat-terns and habitat preference at Ash Meadows National Wildlife Refuge, Nye County, Nevada, USA - Boehme, Nicole F.; Tanner, David A.; Williams, Kevin A.; Pitts, James P. (Zootaxa, 2012)
The diversity of velvet ants at Ash Meadows National Wildlife Refuge (AMNWR) is investigated along with seasonal flight time and habitat preference for each species. Of the 45 (SD ± 2) species expected to occur at AMNWR via first order jackknife estimator, 42 species were found to occur based on 8843 specimens. Variation in flight times between species were minor and revealed a unique pattern of niche partitioning in only one species, Dasymutilla arenivaga Mickel. Habitat preferences were observed for seven species at AMNWR. Dasymutilla arenivaga, Odontophotopsis melicausa (Blake), and Sphaeropthalma orestes (Fox) were found to be more abundant in sand dune habitats than in non-sand dune habitats. While four other species, Odontophotopsis mamata Schuster, O. microdonta Ferguson, O. serca Viereck, and Sphaeropthalma mendica (Blake), were found to be more abundant in non-sand dune habitats. The diversity of velvet ants found at AMNWR was compared to the diversity of velvet ants found at the Nevada Test Site (NTS) located approximately 25 mile northeast of Ash Meadows. This comparison identified six velvet ant species that occurred at the NTS, but were not found at AMNWR. The status of Photopsis nana Ashmead 1896 is reinstanted. New synonymy is proposed for Photopsis nana Ashmead 1896 (=Mutilla acontius Fox, 1899, syn. nov.). Diagnoses and a key are provided for the velvet ants of AMNWR. The hitherto unknown female of Sphaeropthalma megagnathos Schuster is described, and an updated key to the females is provided for S. imperialis species-group. Lectotypes are designated for twelve species.